Effect of self-reported walking difficulty on bone mass and bone resorption marker in Japanese people aged 40 years and over. Issue 1 (December 2016) - Abe, Yasuyo; Nishimura, Takayuki; Arima, Kazuhiko; Kanagae, Mitsuo; Mizukami, Satoshi; Tomita, Yoshihito; Okabe, Takuhiro; Goto, Hisashi; Horiguchi, Itsuko; Aoyagi, Kiyoshi
Abstract Background This study aimed to examine the association of walking difficulty with bone mass or bone turnover among community-dwelling Japanese people aged 40 years and older. Methods We studied 1097 community-dwelling Japanese people aged 40 years and older (379 men and 718 women) who were invited to participate in periodic health examinations in 2006–2009. Walking difficulty was defined as having difficulty walking 100 m on a level surface (self-administered questionnaire). Calcaneal stiffness index (bone mass) was measured by quantitative ultrasound. Spot urine samples were collected, and urinary N-terminal cross-linking telopeptide of type I collagen (NTx) was measured. Values were corrected for creatinine (Cre) concentration. Results The prevalence of walking difficulty was significantly higher in women than in men (7.4 vs. 3.4 %, p  = 0.011) and significantly increased with age in men (p for trend = 0.02) and women (p for trend <0.001). In univariate analysis, men and women with walking difficulty were older (p  < 0.001) and had a lower stiffness index (p  < 0.001), compared with those without walking difficulty. Among women, individuals with walking difficulty had significantly higher urinary NTx/Cre than those without walking difficulty (p  < 0.001); however, this was not so among men (p  = 0.39). Multiple regression analysis adjusted for age, weight, and menopausal status showed a significant association between walking difficulty and lower stiffness index in men (p  = 0.004) and women (p  = 0.005). In women, walking difficulty was significantly associated with higher NTx/Cre (p  = 0.001), but not in men (p  = 0.35). Conclusions Walking difficulty may contribute to low bone mass in both sexes but might cause high bone turnover in women only.